(untitled) (Swiss Medical Weekly, 2022)
AIMS: Anaesthesia safety has improved over time with severe anaesthesia-related complications and death becoming rare events. We investigated anaesthesia-related complications over a period of 17 years in this single centre retrospective observational cohort study. The main aims were to assess the temporal trends of anaesthesia-related complications, their distribution among clinics and their relation to emergency versus non-emergency interventions. METHODS: In this retrospective, observational cohort study, anaesthesia and event protocols of patients who suffered from an anaesthesia-related complication were collected in the period from 1 January 2003 to 31 December 2019. These data sets were anonymised and grouped into demographic information, ASA physical status, information about dental status and hospital department. Out of the total of 257 cases that were reported to the department of anaesthesia at the Luzerner Kantonsspital, 110 were excluded as they were not anaesthesia-related and 14 because of incomplete reporting forms. The different complications were categorised by the severity injury scale score. The total number of anaesthetics during the study period amounted to 399,583. RESULTS: 133 patients with complications were included. Six patients died owing to a partially anaesthesia-related complication, two suffered from permanent damage, 62 had temporary symptoms and in 63 patients dental damage occurred. The temporal trend showed a major decrease in severe anaesthesia complications and deaths, whiledental injuries were the main complications after 2010. Most of the complications were reported in the orthopaedic department, whereas dental injuries were predominantly reported in the otorhinolaryngology department. The majority of complications occurred during elective surgery although this was not significant (p = 0.53). CONCLUSIONS: Severe anaesthesia-related complications and death decreased dramatically during the study period. Anaesthesia complications are not more frequent in emergency surgeries. Overall, complications occurred more frequently in orthopaedics, and dental injuries predominated in otorhinolaryngology.